2007
DOI: 10.1007/s10350-006-0756-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesorectal Grades Predict Recurrences After Curative Resection for Rectal Cancer

Abstract: The macroscopic quality of mesorectum after curative excision of rectal cancer is an important predictor of local and overall recurrences. The mesorectal grades may be of value in decisions regarding postoperative adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
5
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 18 publications
7
90
5
5
Order By: Relevance
“…In a prospective study of 130 patients who underwent curative resection with attempted TME, positive CRM was significantly higher in patients with incomplete TME (29.4%) compared with complete (1.6%) and nearly complete (5.8%) TME (p=0.0001). Local recurrence rose in parallel, from 1.6% and 5.7% respectively after complete and nearly complete TME to 41% after incomplete TME (p=0.0001) (29). The relationship between TME quality, positive CRM, and local recurrence was confirmed by data from the international multicentre CR07 trial which compared the impact of short course preoperative radiotherapy versus selective postoperative chemoradiotherapy on outcomes of patients with resectable Stage I-III rectal cancer (30).…”
Section: The Role Of Surgical Techniquementioning
confidence: 94%
“…In a prospective study of 130 patients who underwent curative resection with attempted TME, positive CRM was significantly higher in patients with incomplete TME (29.4%) compared with complete (1.6%) and nearly complete (5.8%) TME (p=0.0001). Local recurrence rose in parallel, from 1.6% and 5.7% respectively after complete and nearly complete TME to 41% after incomplete TME (p=0.0001) (29). The relationship between TME quality, positive CRM, and local recurrence was confirmed by data from the international multicentre CR07 trial which compared the impact of short course preoperative radiotherapy versus selective postoperative chemoradiotherapy on outcomes of patients with resectable Stage I-III rectal cancer (30).…”
Section: The Role Of Surgical Techniquementioning
confidence: 94%
“…Entre 3% a 35% dos doentes evoluirão com recidiva local. (3,5,6,7,8) Os fatores que estão implicados nas diferentes taxas de recidiva observadas na literatura, são aqueles relacionados à técnica operatória e à própria biologia do tumor. O estadiamento inicial da neoplasia é um dos fatores relacionados à biologia tumoral, sendo considerado o mais importante.…”
Section: Introductionunclassified
“…A ressecção cirúrgica do segmento acometido com adenocarcinoma retal aliada à excisão total do mesorreto (ETM), além da neoadjuvância, tem sido preconizada para o tratamento desta afecção, com redução das taxas de recidiva local. (1,2,3,4,5,6) No entanto, a recidiva pélvica após ressecção curativa do câncer retal, continua influenciando na sobrevida dos doentes, e constituindo importante causa de morbidade pós-operatória. Entre 3% a 35% dos doentes evoluirão com recidiva local.…”
unclassified
“…Besides that, local recurrence depends upon quality of TME which has shown that incomplete TME have local recurrence and was 41%,whereas in near complete it was 6% and in complete TME the rate was less than 2% 14 .…”
Section: Discussionmentioning
confidence: 99%